Російська пропаґанда як елемент підготовки до збройної аґресії проти України - Ільницький, В.; Старка, В.; Галів, М. (Український історичний журнал, 2022)
Мета статті полягає у висвітленні пропаґандистських заходів, які стали
індикатором підготовки збройної аґресії Російської Федерації проти України.
Методологія дослідження побудована на принципах історизму, об’єктивності,
системності, багатофакторності, науковості, використанні загальнонаукових (аналіз,
синтез, наукова абстракція) та спеціально-історичних (історико-генетичний,
історико-типологічний, історико-системний) методів. Наукова новизна полягає у
проведенні комплексного аналізу основних пропаґандистських заходів, здійснюваних
Росією при підготовці до збройної аґресії проти України. Висновки. Готуючись до
нинішньої війни, РФ активно використовувала методи пропаґанди, апробовані під час
підготовки до попередніх воєн. Найважливішими з них стали маніпулювання історією
з метою творення власного історичного міфу; формування «символіки війни», покликаної
«мобілізувати маси» на героїзоване насильство проти українців; дегуманізація
ворога (тобто українців) шляхом невизнання права на розбудову незалежної держави,
заперечення самодостатності української культури, ототожнення українських військовослужбовців
і громадсько-політичних діячів із «нацистами». Російська пропаґанда
фактично леґітимізує геноцид українців та знищення України як держави. Знаходячись
поряд із Росією, українському суспільству варто пам’ятати: російська аґресія проти
українців випливає з глибин колективної пам’яті, проявляючись за кожної слушної нагоди.
Те, що її породжує, здатне лише руйнувати, уподібнюватися чи копіювати, але не
створювати нове. The purpose of the article is to highlight the propaganda activities that became an
indicator of the preparation of the armed aggression of the Russian Federation against Ukraine.
The research methodology is built on the principles of historicism, objectivity, systematicity,
multifactoriality, scientificity, and the use of general scientific (analysis, synthesis, scientific
abstraction) and special-historical (historical-genetic, historical-typological, historical-systemic)
methods. The scientific novelty consists in conducting a comprehensive analysis of the main
propaganda measures carried out by the Russian Federation in preparation for armed aggression
against Ukraine. Conclusions. While preparing for war with Ukraine, the Russian Federation
actively used propaganda methods tested during the preparations for previous wars. The most
important of them in the struggle with Ukraine were: 1) manipulation of history with the aim
of forming one’s own historical myth-building the concept of the “Russian World” / “Russkiy
Mir” with an eclectic combination of pre-revolutionary-imperial and Soviet-communist Russian
narratives; 2) formation of “symbolism of war” designed to mobilize the masses to heroized violence
against Ukrainians: the use of “St. George’s Tape” (and the promotion of its updated semantics),
the creation of appropriate television, audio and film productions with the aim of glorifying
and heroizing the “a Russian soldier”, his “right struggle”; 3) dehumanization of the enemy (in
this case, Ukrainians) by, firstly, not recognizing the right to build an independent Ukrainian
state; secondly, denial of the self-sufficiency of Ukrainian culture; thirdly, the identification of
Ukrainian military and public and political figures with the “Nazis”. Russian propaganda actually
legitimizes the genocide of Ukrainians and the destruction of the Ukrainian state. Living next to
Russia, Ukrainian society should always remember: Russian aggression towards Ukrainians flows
from the depths of collective memory, manifesting itself on the right occasion. What generates it
can only destroy, assimilate or copy, but not create new.